Cranial anatomy of tadpoles of five species of Scinax (Hylidae, Hylinae) - Alcalde, Leandro; Candioti, Florencia Vera; Kolenc, Francisco; Borteiro, Claudio; Baldo, Diego (Zootaxa, 2011)
We studied the oral apparatus, buccal cavity and musculoskeletal features in tadpoles of five species of the genus Scinax (S. acuminatus, S. uruguayus, S. aff. pinima, S. aromothyella, and S. berthae). Observed variation is mainly related to intrageneric grouping. Scinax acuminatus (S. ruber clade, sister taxon of S. rostratus group) has a distinctive combination of a mental gap in the margin of oral papillae, straight labial teeth with few or absent cusps, processus muscularis acute and posteriorly directed, and m. subarcualis rectus I with two slips. Scinax uruguayus and S. aff. pinima (S. uruguayus group) have keratinized sheets ventrolateral to the lower jaw sheath, well-developed infralabial and lateral ridge papillae, robust jaw cartilages, cornua trabeculae with short and widely divergent free portions, processus articularis short and wide, processus muscularis thin and directed anteriorly. Scinax aromothyella and S. berthae (S. catharinae group) have poorly developed, non-colored spurs behind the lower jaw sheath, long and thin processus articularis, wide and rounded processus muscularis, and tripartite cartilago suprarostralis. Anatomical features described are congruent with current phylogenetic arrangements based on molecular, chromosomal, and morphological data, and provide a source of information that can be useful to solve interspecific relationships within Scinax.